Assessment of total evaporation rates and its surface distribution by tridimensional modelling and remote sensing. (1st February 2023) - Rocha, Sofia M.G.; Molinas, Ernesto; Rodrigues, Italo S.; Lima Neto, Iran E.
Abstract: In arid and semiarid environments, evaporation is responsible for significant water losses from reservoirs. This condition is of special concern in the Brazilian Northeast region, as this is one of the most populous semiarid areas in the planet. The present study aims to assess the spatio-temporal variability of evaporation rates on the water surface of Pentecoste reservoir, located in the Brazilian semiarid region, by using both the hydrodynamic model Delft3D and a remote sensing technique (RS). While RS has already been used to evaluate the spatial distribution of evaporation rates in lakes, Delft3D was innovatively tested and applied for this purpose for the first time in this study. The calibration results showed an accurate reproduction of the water level variability (r 2 of 0.997), along with a satisfactory calibration of the reservoir's thermal structure for the full water column (MAE of 0.539 °C, RMSE of 0.572 °C, and NMAE of 0.008). Curves relating monthly evaporation rates with air temperature and wind speed showed strong correlation between those variables (r 2 of 0.817 for air temperature and 0.849 for wind speed). Also, the averaged evaporation rates modeled by Delft3D differed by less than 5% compared to RS. Regarding the spatial distribution results, for the wet period the evaporation patterns were similar to those of RS, while in the dry period RS provided a more stable evaporation pattern when compared to Delft3D. The innovative approach proposed in the present study can be used to better understand the evaporation dynamics in surface waters and optimize the location of damping evaporation structures, namely air diffusers, shading systems, and floating solar panels, which are important for improving water availability, not only in drylands. Highlights: 3D modelling was innovatively used to predict surface evaporation in a reservoir. The model reproduced well the water level variation and reservoir stratification. The spatial distribution of evaporation was comparable to that from remote sensing. Evaporation rates correlated well with both air temperature and wind speed.